THERMOACOUSTIC STUDIES IN ALKENYL LIQUID CRYSTALLINE COMPOUNDS - Nagesh, A.; Sailaja, D.; Reddy, K.Chandrasekhar (IJRDO-Journal of Applied Science, 2016)
Density of the liquid crystals can bemeasured by using a specially constructedsensitive dilatometer having two uniformlybored capillary arms of length around 30 cmabove the bulb The volume of thedilatometer bulb and the volume of thecapillary bore per cm were determined bycalibrating it with triple distilled water,benzene and mercury and found to be3.12916 cc and 0.00951 cc/cm respectively.The levels of the fluid in both capillary armswere recorded by using two travelingmicroscopes of least count 0.001 cm. Thetemperature variations of the volume of thedilatometer were recorded and correctionswere made for it. All the weighing weredone on sensitive K.Roy analytical singlepan balance of sensitivity 0.00005 gm. Thedilatometer was placed inside the INSREFsolid state temperature bath and thetemperature was controlled to an accuracy of 0.1C for making measurements at varioustemperatures.